Source-to-sink redistribution of critical elements from a granite–bauxite provenance in the fluvial peat system of Tayan Peatland, West Kalimantan: An analogue model for critical element enrichment in coals - Ferian Anggara; Mochamad Fachruddin Yusra; Salman Al Farizi; Yunanto Budi Prasetyo; Aldian Fahrialam; Esti Handini; Yan Restu Freski; Himawan Tri Bayu Murti Petrus; Tim A. Moore; Aulia Agus Patria (International Journal of Coal Geology, 2026)

Organic petrological and geochemical controls on critical element distribution in peat influenced by rhyolitic basement rocks from the Sebangau Peatland, Central Kalimantan: An analogue model for critical element enrichment in coals - Ferian Anggara; Shifeng Dai; Tim A. Moore; Auvanda Ivan Muhammad; Ofentse M. Moroeng; Jingjing Liu; Aldian Fahrialam; Himawan Tri Bayu Murti Petrus; Aulia Agus Patria (International Journal of Coal Geology, 2026)

Coal bed gas in Colombia: Current status - Jorge Eliecer Mariño-Martinez; Tim A. Moore; Juan Sebastian Gomez-Neita (International Journal of Coal Geology, 2026)

Biomarkers and organic carbon isotopes in Pennsylvanian–Early Permian coals of the Ordos Basin: Implications for palaeoenvironmental evolution in North China - Yang Liang; Wei Yuan; Jingjing Liu; Victor P. Nechaev; Tim A. Moore; Shaowei Zhang; Qian Wang; Jintian Zheng; Xiaoyun Yan; Mengda Yao; Shuai Kang; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Petrological, mineralogical, and geochemical compositions of the Eocene coals from Senakin Peninsula, South Kalimantan, Indonesia - Ferian Anggara; Donatus Hendra Amijaya; Tim A. Moore; Azmii Nanda Fadhillah; Aulia Agus Patria (International Journal of Coal Geology, 2025)

Isotopic and petrographic implications for fire type, temperature and formation of degradosemifusinite in fusain layers from an Early Cretaceous coal bed, Hailar Basin, Inner Mongolia, China - Ofentse M. Moroeng; Tim A. Moore; Jian Shen; Joan S. Esterle; Jingjing Liu (Fuel, 2025)

Tree Diversity Increases Carbon Stocks and Fluxes Above—But Not Belowground in a Tropical Forest Experiment - Florian Schnabel; Joannès Guillemot; Kathryn E. Barry; Melanie Brunn; Simone Cesarz; Nico Eisenhauer; Tobias Gebauer; Nathaly R. Guerrero‐Ramirez; I. Tanya Handa; Chris Madsen; Lady Mancilla; Jose Monteza; et al. (Global Change Biology, 2025)
International commitments advocate large‐scale forest restoration as a nature‐based solution to climate change mitigation through carbon (C) sequestration. Mounting evidence suggests that mixed compared to monospecific planted forests may sequester more C, exhibit lower susceptibility to climate extremes and offer a broader range of ecosystem services. However, experimental studies comprehensively examining the control of tree diversity on multiple C stocks and fluxes above‐ and belowground are lacking. To address this gap, we leverage data from the Sardinilla experiment in Panama, the oldest tropical tree diversity experiment, which features a gradient of one‐, two‐, three‐ and five‐species mixtures of native tree species. Over 16 years, we measured multiple above‐ and belowground C stocks and fluxes, ranging from tree aboveground C, over leaf litter C production, to soil organic carbon (SOC). We show that tree diversity significantly increased aboveground C stocks and fluxes, with a 57% higher gain in aboveground tree C in five‐species mixtures compared to monocultures (35.7 ± 1.8 vs. 22.8 ± 3.4 Mg C ha −1 ) 16 years after planting. In contrast, we observed a net reduction in SOC (on average −11.2 ± 1.1 Mg C ha −1 across diversity levels) and no significant difference in SOC 3 stocks (the predominantly tree‐derived, i.e., C 3 plant‐derived SOC fraction) between five‐species mixtures and monocultures (13.0 ± 0.9 vs. 15.1 ± 1.3 Mg C ha −1 ). Positive tree diversity effects persisted despite repeated climate extremes and strengthened over time for aboveground tree growth. Structural equation models showed that higher tree growth in mixtures enhanced leaf litter and coarse woody debris C fluxes to the soil, resulting in a tightly linked C cycle aboveground. However, we did not observe significant links between above‐ and belowground C stocks and fluxes. Our study elucidates the mechanisms through which higher tree diversity bolsters the climate mitigation potential of tropical forest restoration. Restoration schemes should prioritize mixed over monospecific planted forests.

Coalbed gas: A review of research directions from the past to the future as facilitated by bibliometrics - Romeo M. Flores; Tim Moore (International Journal of Coal Geology, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Estimating sediment delivery ratio using the RUSLE-IC-SDR approach at a complex landscape: A case study at the Lower Snowy River area, Australia - Xihua Yang; John Young; Haijing Shi; Qinggaozi Zhu; Ian Pulsford; Greg Chapman; Leah Moore; Angela G Gormley; Richard Thackway; Tim Shepherd (Journal of Hydrology, 2024)

Horticultural additives influence peat biogeochemistry and increase short-term CO2 production from peat - Bidhya Sharma; Tim R. Moore; Klaus-Holger Knorr; Henning Teickner; Peter M. J. Douglas; Nigel T. Roulet (Plant and Soil, 2024)
Aims Peat is used as a major ingredient of growing media in horticulture. Peat extracted from bogs can be acidic and low in nutrient availability and is therefore mixed with liming agents, nutrients, surfactants, perlite and so on. This study aims to estimate the rates at which raw peat and the modified peat (‘growing media’) decompose to release carbon dioxide (CO 2 ), to estimate the release of carbon (C) from liming agents and to estimate how peat biogeochemistry is changed. Methods We obtained 28 and 24 samples of raw peat and 24 growing media from four peat extraction companies in Canada. Growing media were treated with horticultural additives. We incubated the samples under laboratory conditions, measuring CO 2 production, tracer using $${\updelta }^{13}{\text{C}}$$ δ 13 C - $${{\text{CO}}}_{2}$$ CO 2 , pH, C, nitrogen (N) content and humification indices (HIs) from infrared technology called Fourier transform-mid infrared (FT-MIR). Results C:N ratio, pH, dissolved organic carbon, bulk density and C content differed significantly ( P < 0.05) between raw peats and growing media. There was more than a doubling of total $${{\text{CO}}}_{2}$$ CO 2 production from growing media compared to raw peat. HIs show higher values for the growing media, which could result from spectral band shifts in the growing media because of increased cation availability. $${\updelta }^{13}{\text{C}}$$ δ 13 C - $${{\text{CO}}}_{2}$$ CO 2 as a tracer showed an average 22% of the total $${{\text{CO}}}_{2}$$ CO 2 production orginated from added carbonate materials. Conclusion Our results provide the rates (0.15 ± 0.017mgCO 2 -Cg −1 d −1 ) at which horticultural peat decomposes and on the source of emitted $${{\text{CO}}}_{2}$$ CO 2 . This will improve current estimates CO 2 emissions from horticultural peat.

Peatland Fungal Community Responses to Nutrient Enrichment: A Story Beyond Nitrogen - Meng Wang; Louis J. Lamit; Erik A. Lilleskov; Nathan Basiliko; Tim R. Moore; Jill L. Bubier; Galen Guo; Sari Juutinen; Tuula Larmola (Global Change Biology, 2024)
Anthropogenically elevated inputs of nitrogen (N), phosphorus (P), and potassium (K) can affect the carbon (C) budget of nutrient‐poor peatlands. Fungi are intimately tied to peatland C budgets due to their roles in organic matter decomposition and symbioses with primary producers; however, the influence of fertilization on peatland fungal composition and diversity remains unclear. Here, we examined the effect of fertilization over 10 years on fungal diversity, composition, and functional guilds along an acrotelm (10–20 cm), mesotelm (30–40 cm), and catotelm (60–70 cm) depth gradient at the Mer Bleue bog, Canada. Simultaneous N and PK additions decreased the relative abundance of ericoid mycorrhizal fungi and increased ectomycorrhizal fungi and lignocellulose‐degrading fungi. Fertilization effects were not more pronounced in the acrotelm relative to the catotelm, nor was there a shift toward nitrophilic taxa after N addition. The direct effect of fertilization significantly decreased the abundance of Sphagnum ‐associated fungi, primarily owing to the overarching role of limiting nutrients rather than a decline in Sphagnum cover. Increased nutrient loading may threaten peatland C stocks if lignocellulose‐degrading fungi become abundant and accelerate decomposition of recalcitrant organic matter. Additionally, future changes in plant communities, strong water table fluctuations, and peat subsidence after long‐term nutrient loading may also influence fungal functional guilds and depth‐dependencies of fungal community structure.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The fish–mangrove link is context dependent: Tidal regime and reef proximity determine the ecological role of tropical mangroves - Michael Bradley; Alexia Dubuc; Camilla V. H. Piggott; Katie Sambrook; Andrew S. Hoey; Martial Depczynski; Tim J. Langlois; Monica Gagliano; Shaun K. Wilson; Katherine Cure; Thomas H. Holmes; Glenn I. Moore; et al. (Fish and Fisheries, 2024)
Tropical mangroves are known to support fish production, but natural variability in the link between mangrove habitats and fish populations undermines our ability to manage, conserve and restore this ecological relationship. This is largely due to undefined context‐dependence in the use of mangroves by fish. We collected a spatially extensive dataset of 494 mangrove fish assemblages using standardised Remote Underwater Video surveys of mangrove edge habitats from five environmentally heterogenous regions in the Indo‐Pacific. We used machine learning methods to define contextual limits of the use of mangroves by reportedly mangrove‐affiliated fish. We found that tidal range and proximity to coral reefs were the most important contextual predictors of the use of mangroves by most taxa. We established data‐driven threshold values for important contextual predictors of the use of mangroves by fish, offering new insights into the variable role played by tropical mangroves in supporting fish life histories. Where mangroves occur as part of reef seascapes in regions with limited tidal range (

Fire activities and their impacts on local ecosystems in the southern Ordos Basin during the Middle Jurassic: Evidence from pyrogenic PAHs and petrography of inertinite-rich coal - Qiuchan Han; Jingjing Liu; James C. Hower; Tim A. Moore; Niande Shang; Shumao Zhao; Rongkun Jia; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

Mechanistic simulations of kelp populations in a dynamic landscape of light, temperature, and winter storms - Tim M. Szewczyk; Pippa J. Moore; Dan A. Smale; Thomas Adams; Michael T. Burrows (Ecological Modelling, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

Geochemical and mineralogical responses to thermal alteration by an igneous intrusion in the Dashucun Coal Mine of the Fengfeng coalfield, Hebei, North China - Na Wang; Shifeng Dai; Joan Esterle; Tim Moore; Lei Zhao (Applied Geochemistry, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Proceedings of the 38th Annual Conference of The Society for Organic Petrology: Organics in the geological cycle - Tim A. Moore; Carme Huguet; Ofentse M. Moroeng; Carol I. Sule (International Journal of Coal Geology, 2023)

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

How should we judge edible oils and fats? An umbrella review of the health effects of nutrient and bioactive components found in edible oils and fats - Scott B. Teasdale; Skye Marshall; Kylie Abbott; Tim Cassettari; Emily Duve; Flavia Fayet-Moore (Critical Reviews in Food Science and Nutrition, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Niche and neutral assembly mechanisms contribute to latitudinal diversity gradients in reef fishes - Nestor E. Bosch; Thomas Wernberg; Tim J. Langlois; Dan A. Smale; Pippa J. Moore; João N. Franco; Pierre Thiriet; Eric Feunteun; Cláudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee‐Dexter; et al. (Journal of Biogeography, 2021)
Aim The influence of niche and neutral mechanisms on the assembly of ecological communities have long been debated. However, we still have a limited knowledge on their relative importance to explain patterns of diversity across latitudinal gradients (LDG). Here, we investigate the extent to which these ecological mechanisms contribute to the LDG of reef fishes. Location Eastern Atlantic Ocean. Taxon Reef‐associated ray‐finned fishes. Methods We combined abundance data across ~60° of latitude with functional trait data and phylogenetic trees. A null model approach was used to decouple the influence of taxonomic diversity (TD) on functional (FD) and phylogenetic (PD) diversity. Standardized effect sizes (SES FD and SES PD) were used to explore patterns of overdispersion, clustering and randomness. Information theoretic approaches were used to investigate the role of large‐ (temperature, geographic isolation, nitrate and net primary productivity) and local‐scale (human population and depth) drivers. We further assessed the role of demographic stochasticity and its interaction with species trophic identity and dispersal capacity. Results Taxonomic diversity peaked at ~15°–20°N, with a second mode of lower magnitude at ~45°N; a pattern that was predicted by temperature, geographic isolation and productivity. Tropical regions displayed a higher proportion of overdispersed assemblages, whilst clustering increased towards temperate regions. Phylogenetic and functional overdispersion were associated with warmer, productive and isolated regions. Demographic stochasticity also contributed largely to community assembly, independently of ecoregions, although variation was dependent on the trophic identity and body size of species. Main conclusions Niche‐based processes linking thermal and resource constraints to local coexistence mechanisms have contributed to the LDG in reef fishes. These processes do not act in isolation, stressing the importance of understanding interactions between deterministic and stochastic factors driving community structure in the face of rapid biodiversity change.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Mechanisms for the Development of Microform Patterns in Peatlands of the Hudson Bay Lowland - Lorna I. Harris; Nigel T. Roulet; Tim R. Moore (Ecosystems, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Preface: Advances in hydrogeologic understanding of Australia’s Great Artesian Basin - Carlos Miraldo Ordens; Neil McIntyre; Jim R. Underschultz; Tim Ransley; Catherine Moore; Dirk Mallants (Hydrogeology Journal, 2020)

Plant and Soil Nitrogen in an Ombrotrophic Peatland, Southern Canada - Tim R. Moore; Jill L. Bubier (Ecosystems, 2020)

Orchid fleck virus associated with the first case of citrus leprosis-N in South Africa - Glynnis Cook; Wayne Kirkman; Rochelle Clase; Chanel Steyn; Elaine Basson; Paul H. Fourie; Sean D. Moore; Tim G. Grout; Elma Carstens; Vaughan Hattingh (European Journal of Plant Pathology, 2019)

Coastal Harmful Algae Bloom Monitoring via a Sustainable, Sail-Powered Mobile Platform - Jordon S. Beckler; Ethan Arutunian; Tim Moore; Bob Currier; Eric Milbrandt; Scott Duncan (Frontiers in Marine Science, 2019)

The Spatial Heterogeneity of Vegetation, Hydrology and Water Chemistry in a Peatland with Open-Water Pools - Julien Arsenault; Julie Talbot; Tim R. Moore; Marie-Pierre Beauvais; Jan Franssen; Nigel T. Roulet (Ecosystems, 2019)

Mapping resistance to Phytophthora root rot identifies independent loci from cultivated (Cicer arietinum L.) and wild (Cicer echinospermum P.H. Davis) chickpea - Amritha Amalraj; Julian Taylor; Sean Bithell; Yongle Li; Kevin Moore; Kristy Hobson; Tim Sutton (Theoretical and Applied Genetics, 2019)

Plant uptake of organic nitrogen in two peatlands - Tim R. Moore; Amanda Alfonso; Beverley R. Clarkson (Plant and Soil, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Resources and geology of coalbed methane in China: a review - Yong Qin; Tim A. Moore; Jian Shen; Zhaobiao Yang; Yulin Shen; Geoff Wang (International Geology Review, 2018)

Changes from pasture to a native tree plantation affect soil organic matter in a tropical soil, Panamá - Tim R. Moore; Muriel Abraham; Margaret Kalácska; Meaghan T. Murphy; Catherine Potvin (Plant and Soil, 2018)

Can short-term litter-bag measurements predict long-term decomposition in northern forests? - Tim R. Moore; J. A. Trofymow; C. E. Prescott; B. D. Titus (Plant and Soil, 2017)

Passive acoustic monitoring of the decline of Mexico's critically endangered vaquita - Armando Jaramillo‐Legorreta; Gustavo Cardenas‐Hinojosa; Edwyna Nieto‐Garcia; Lorenzo Rojas‐Bracho; Jay Ver Hoef; Jeffrey Moore; Nicholas Tregenza; Jay Barlow; Tim Gerrodette; Len Thomas; Barbara Taylor (Conservation Biology, 2017)
The vaquita (Phocoena sinus) is the world's most endangered marine mammal with approximately 245 individuals remaining in 2008. This species of porpoise is endemic to the northern Gulf of California, Mexico, and historically the population has declined because of unsustainable bycatch in gillnets. An illegal gillnet fishery for an endangered fish, the totoaba (Totoaba macdonaldi) , has recently resurged throughout the vaquita's range. The secretive but lucrative wildlife trade with China for totoaba swim bladders has probably increased vaquita bycatch mortality by an unknown amount. Precise population monitoring by visual surveys is difficult because vaquitas are inherently hard to see and have now become so rare that sighting rates are very low. However, their echolocation clicks can be identified readily on specialized acoustic detectors. Acoustic detections on an array of 46 moored detectors indicated vaquita acoustic activity declined by 80% between 2011 and 2015 in the central part of the species’ range. Statistical models estimated an annual rate of decline of 34% (95% Bayesian credible interval –48% to –21%). Based on results from 2011 to 2014, the government of Mexico enacted and is enforcing an emergency 2‐year ban on gillnets throughout the species’ range to prevent extinction, at a cost of US$74 million to compensate fishers. Developing precise acoustic monitoring methods proved critical to exposing the severity of vaquitas’ decline and emphasizes the need for continual monitoring to effectively manage critically endangered species.

Biodegradability of Vegetation-Derived Dissolved Organic Carbon in a Cool Temperate Ombrotrophic Bog - Andrew J. Pinsonneault; Tim R. Moore; Nigel T. Roulet; Jean-François Lapierre (Ecosystems, 2016)

Stoichiometric response of shrubs and mosses to long-term nutrient (N, P and K) addition in an ombrotrophic peatland - Meng Wang; Tuula Larmola; Meaghan T. Murphy; Tim R. Moore; Jill L. Bubier (Plant and Soil, 2016)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Carbon, Nitrogen, Phosphorus, and Potassium Stoichiometry in an Ombrotrophic Peatland Reflects Plant Functional Type - Meng Wang; Tim R. Moore (Ecosystems, 2014)

Distribution and diversity of V errucomicrobia methanotrophs in geothermal and acidic environments - Christine E. Sharp; Angela V. Smirnova; Jaime M. Graham; Matthew B. Stott; Roshan Khadka; Tim R. Moore; Stephen E. Grasby; Maria Strack; Peter F. Dunfield (Environmental Microbiology, 2014)
Summary Recently, methanotrophic members of the phylum V errucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16 S rRNA gene amplicons. Putative methanotrophic V errucomicrobia were found in samples covering a broad temperature range (22.5–81.6° C ), but only in acidic conditions ( pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16 S rRNA gene sequence clusters of putative methanotrophic V errucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6° C ) grouped with known thermoacidiphilic ‘ M ethylacidiphilum ’ isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1° C ) and a representative mesophilic methanotroph from this group was isolated (strain LP 2 A ). Genome sequencing verified that strain LP 2 A possessed particulate methane monooxygenase, but its 16 S rRNA gene sequence identity to ‘ M ethylacidiphilum infernorum ’ strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic V errucomicrobia . Using pmoA ‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP 2 A ‐like pmoA sequences in the cooler surface layers and ‘ M ethylacidiphilum'‐ like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic V errucomicrobia . However, both were detected only in acidic geothermal environments.

Water Table Regime Regulates Litter Decomposition in Restiad Peatlands, New Zealand - Beverley R. Clarkson; Tim R. Moore; Neil B. Fitzgerald; Danny Thornburrow; Corinne H. Watts; Steven Miller (Ecosystems, 2014)

Nutrient resorption of two evergreen shrubs in response to long-term fertilization in a bog - Meng Wang; Meaghan T. Murphy; Tim R. Moore (Oecologia, 2014)

Vegetation feedbacks of nutrient addition lead to a weaker carbon sink in an ombrotrophic bog - Tuula Larmola; Jill L. Bubier; Christine Kobyljanec; Nathan Basiliko; Sari Juutinen; Elyn Humphreys; Michael Preston; Tim R. Moore (Global Change Biology, 2013)
To study vegetation feedbacks of nutrient addition on carbon sequestration capacity, we investigated vegetation and ecosystem CO 2 exchange at Mer Bleue Bog, Canada in plots that had been fertilized with nitrogen (N) or with N plus phosphorus (P) and potassium (K) for 7–12 years. Gross photosynthesis, ecosystem respiration, and net CO 2 exchange were measured weekly during May–September 2011 using climate‐controlled chambers. A substrate‐induced respiration technique was used to determine the functional ability of the microbial community. The highest N and NPK additions were associated with 40% less net CO 2 uptake than the control. In the NPK additions, a diminished C sink potential was due to a 20–30% increase in ecosystem respiration, while gross photosynthesis rates did not change as greater vascular plant biomass compensated for the decrease in Sphagnum mosses. In the highest N‐only treatment, small reductions in gross photosynthesis and no change in ecosystem respiration led to the reduced C sink. Substrate‐induced microbial respiration was significantly higher in all levels of NPK additions compared with control. The temperature sensitivity of respiration in the plots was lower with increasing cumulative N load, suggesting more labile sources of respired CO 2 . The weaker C sink potential could be explained by changes in nutrient availability, higher woody : foliar ratio, moss loss, and enhanced decomposition. Stronger responses to NPK fertilization than to N‐only fertilization for both shrub biomass production and decomposition suggest that the bog ecosystem is N‐P/K colimited rather than N‐limited. Negative effects of further N‐only deposition were indicated by delayed spring CO 2 uptake. In contrast to forests, increased wood formation and surface litter accumulation in bogs seem to reduce the C sink potential owing to the loss of peat‐forming Sphagnum .

Evaluating and predicting risk to a large reptile (Varanus varius) from feral cat baiting protocols - Tim S. Jessop; Michael R. Kearney; Joslin L. Moore; Tim Lockwood; Michael Johnston (Biological Invasions, 2013)

Effects of nutrient addition on leaf chemistry, morphology, and photosynthetic capacity of three bog shrubs - Jill L. Bubier; Rose Smith; Sari Juutinen; Tim R. Moore; Rakesh Minocha; Stephanie Long; Subhash Minocha (Oecologia, 2011)

A Multi-Year Record of Methane Flux at the Mer Bleue Bog, Southern Canada - Tim R. Moore; Allison De Young; Jill L. Bubier; Elyn R. Humphreys; Peter M. Lafleur; Nigel T. Roulet (Ecosystems, 2011)

Nature and nurture in the dynamics of C, N and P during litter decomposition in Canadian forests - Tim R. Moore; J. A. Trofymow; Cindy E. Prescott; B. D. Titus (Plant and Soil, 2011)

Linking root production to aboveground plant characteristics and water table in a temperate bog - Meaghan Thibault Murphy; Tim R. Moore (Plant and Soil, 2010)

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

Responses of Vegetation and Ecosystem CO2 Exchange to 9 Years of Nutrient Addition at Mer Bleue Bog - Sari Juutinen; Jill L. Bubier; Tim R. Moore (Ecosystems, 2010)

Carbon dioxide, methane, and nitrous oxide exchanges in an age‐sequence of temperate pine forests - MATTHIAS PEICHL; M. ALTAF ARAIN; SAMI ULLAH; TIM R. MOORE (Global Change Biology, 2010)
We investigated soil carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) exchanges in an age‐sequence (4, 17, 32, 67 years old) of eastern white pine ( Pinus strobus L.) forests in southern Ontario, Canada, for the period of mid‐April to mid‐December in 2006 and 2007. For both CH 4 and N 2 O, we observed uptake and emission ranging from −160 to 245 μg CH 4 m −2 h −1 and −52 to 21 μg N 2 O m −2 h −1 , respectively (negative values indicate uptake). Mean fluxes from mid‐April to mid‐December across the 4, 17, 32, 67 years old stands were similar for CO 2 fluxes (259, 246, 220, and 250 mg CO 2 m −2 h −1 , respectively), without pattern for N 2 O fluxes (−3.7, 1.5, −2.2, and −7.6 μg N 2 O m −2 h −1 , respectively), whereas the uptake rates of CH 4 increased with stand age (6.4, −7.9, −10.8, and −23.3 μg CH 4 m −2 h −1 , respectively). For the same period, the combined contribution of CH 4 and N 2 O exchanges to the global warming potential (GWP) calculated from net ecosystem exchange of CO 2 and aggregated soil exchanges of CH 4 and N 2 O was on average 4%, 2 fluxes correlated positively with soil temperature but had no relationship with soil moisture. We found no control of soil temperature or soil moisture on CH 4 and N 2 O fluxes, but CH 4 emission was observed following summer rainfall events. LFH layer removal reduced CO 2 emissions by 43%, increased CH 4 uptake during dry and warm soil conditions by more than twofold, but did not affect N 2 O flux. We suggest that significant alternating sink and source potentials for both CH 4 and N 2 O may occur in N‐ and soil water‐limited forest ecosystems, which constitute a large portion of forest cover in temperate areas.

Effects of Water Table Drawdown on Root Production and Aboveground Biomass in a Boreal Bog - Meaghan Murphy; Raija Laiho; Tim R. Moore (Ecosystems, 2009)

Litter decomposition and nitrogen and phosphorus dynamics in peatlands and uplands over 12 years in central Canada - Tim R. Moore; J. A. Trofymow; M. Siltanen; L. M. Kozak (Oecologia, 2008)

Production of Dissolved Organic Carbon in Canadian Forest Soils - Tim R. Moore; David Paré; Robert Boutin (Ecosystems, 2008)

Regulation of Decomposition and Methane Dynamics across Natural, Commercially Mined, and Restored Northern Peatlands - Nathan Basiliko; Christian Blodau; Charlotte Roehm; Per Bengtson; Tim R. Moore (Ecosystems, 2007)

A participatory approach to the establishment of a baseline scenario for a reforestation Clean Development Mechanism project - Catherine Potvin; Petra Tschakert; Frédéric Lebel; Kate Kirby; Hector Barrios; Judith Bocariza; Jaime Caisamo; Leonel Caisamo; Charianito Cansari; Juan Casamá; Maribel Casamá; Laura Chamorra; et al. (Mitigation and Adaptation Strategies for Global Change, 2007)

Litter Decomposition in Temperate Peatland Ecosystems: The Effect of Substrate and Site - Tim R. Moore; Jill L. Bubier; Leszek Bledzki (Ecosystems, 2007)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

Effects of nutrient addition on vegetation and carbon cycling in an ombrotrophic bog - JILL L. BUBIER; TIM R. MOORE; LESZEK A. BLEDZKI (Global Change Biology, 2007)
We measured net ecosystem CO 2 exchange (NEE), plant biomass and growth, species composition, peat microclimate, and litter decomposition in a fertilization experiment at Mer Bleue Bog, Ottawa, Ontario. The bog is located in the zone with the highest atmospheric nitrogen deposition for Canada, estimated at 0.8–1.2 g N m −2 yr −1 (wet deposition as NH 4 and NO 3 ). To establish the effect of nutrient addition on this ecosystem, we fertilized the bog with six treatments involving the application of 1.6–6 g N m −2 yr −1 (as NH 4 NO 3 ), with and without P and K, in triplicate 3 m × 3 m plots. The initial 5–6 years have shown a loss of first Sphagnum , then Polytrichum mosses, and an increase in vascular plant biomass and leaf area index. Analyses of NEE, measured in situ with climate‐controlled chambers, indicate that contrary to expectations, the treatments with the highest levels of nutrient addition showed lower rates of maximum NEE and gross photosynthesis, but little change in ecosystem respiration after 5 years. Although shrub biomass and leaf area increased in the high nutrient plots, loss of moss photosynthesis owing to nutrient toxicity, increased vascular plant shading and greater litter accumulation contributed to the lower levels of CO 2 uptake. Our study highlights the importance of long‐term experiments as we did not observe lower NEE until the fifth year of the experiment. However, this may be a transient response as the treatment plots continue to change. Higher levels of nutrients may cause changes in plant composition and productivity and decrease the ability of peatlands to sequester CO 2 from the atmosphere.

Dissolved organic carbon in New Zealand peatlands - Tim R. Moore; Beverley R. Clarkson (New Zealand Journal of Marine and Freshwater Research, 2007)
We determined the concentration of dissolved organic carbon (DOC) and the specific ultraviolet absorbance (SUVA) of 193 samples of water collected from groundwater, porewater, drainage ditches, and streams at peatlands in New Zealand. There was a wide range in DOC concentration (from 7 to 184 mg litre –1 ), with the smallest concentrations in peatlands where there appeared to be large amounts of iron. Concentrations were large (generally >50 mg litre –1 ) in ombrotrophic (rain‐fed) peatlands and reached the highest values (averaging 81 to 129 mg litre –1 ) in water collected from the Torehape peatland (Waikato region), which is undergoing drainage and harvesting for peat and post‐harvest restoration. These high DOC concentrations suggest that New Zealand peatlands export 10 to 50 g DOC m –2 yr –1 , a significant part of the overall carbon budget of peatlands. Most SUVA measurements ranged from 1.5 to 3.5 litre/mg DOC ‐1 /m –1 ) and suggest that the DOC contains 12 to 25% aromatics.

Contemporary carbon balance and late Holocene carbon accumulation in a northern peatland - NIGEL T. ROULET; PETER M. LAFLEUR; PIERRE J. H. RICHARD; TIM R. MOORE; ELYN R. HUMPHREYS; JILL BUBIER (Global Change Biology, 2007)
Northern peatlands contain up to 25% of the world's soil carbon (C) and have an estimated annual exchange of CO 2 ‐C with the atmosphere of 0.1–0.5 Pg yr −1 and of CH 4 ‐C of 10–25 Tg yr −1 . Despite this overall importance to the global C cycle, there have been few, if any, complete multiyear annual C balances for these ecosystems. We report a 6‐year balance computed from continuous net ecosystem CO 2 exchange (NEE), regular instantaneous measurements of methane (CH 4 ) emissions, and export of dissolved organic C (DOC) from a northern ombrotrophic bog. From these observations, we have constructed complete seasonal and annual C balances, examined their seasonal and interannual variability, and compared the mean 6‐year contemporary C exchange with the apparent C accumulation for the last 3000 years obtained from C density and age‐depth profiles from two peat cores. The 6‐year mean NEE‐C and CH 4 ‐C exchange, and net DOC loss are −40.2±40.5 (±1 SD), 3.7±0.5, and 14.9±3.1 g m −2 yr −1 , giving a 6‐year mean balance of −21.5±39.0 g m −2 yr −1 (where positive exchange is a loss of C from the ecosystem). NEE had the largest magnitude and variability of the components of the C balance, but DOC and CH 4 had similar proportional variabilities and their inclusion is essential to resolve the C balance. There are large interseasonal and interannual ranges to the exchanges due to variations in climatic conditions. We estimate from the largest and smallest seasonal exchanges, quasi‐maximum limits of the annual C balance between 50 and −105 g m −2 yr −1 . The net C accumulation rate obtained from the two peatland cores for the interval 400–3000 bp (samples from the anoxic layer only) were 21.9±2.8 and 14.0±37.6 g m −2 yr −1 , which are not significantly different from the 6‐year mean contemporary exchange.

Spring photosynthesis in a cool temperate bog - TIM R. MOORE; PETER M. LAFLEUR; DIANE M. I. POON; BENJAMIN W. HEUMANN; J. W. SEAQUIST; NIGEL T. ROULET (Global Change Biology, 2006)
In northern ecosystems, the onset and growth of spring photosynthesis may have an important influence on the annual carbon (C) budget, yet the controls have not been clearly identified, especially for peatlands. We used a 5‐year set of daily carbon dioxide (CO 2 ) exchange measurements derived from an eddy covariance tower located at Mer Bleue, an ombrotrophic bog near Ottawa, Canada, from March to May [day‐of‐year (DOY) 60–150], 1999–2003. We used half‐hourly measured net ecosystem exchange minus modelled ecosystem respiration to estimate daily photosynthesis, as gross ecosystem production (GEP). The onset of GEP in each year was closely related to the thinning and disappearance of the snow cover, occurring between DOY 86 and 101. GEP increased during the spring, reaching 10‐day average values of between 5 and 9 g CO 2 m −2 day −1 by the end of May. This increase was initially associated with moss activity ( Sphagnum and Polytrichum ), followed by the evergreen shrubs. Peat temperatures in the rooting zone (10–20 cm depth) and increases in shrub leaf nitrogen and chlorophyll a concentrations contributed to this rapid increase in GEP. Examination of moderate‐resolution imaging spectroradiometer (MODIS) images over several years revealed that the temporal resolution (16‐day composites) was inadequate to capture the onset of GEP but estimates of gross primary productivity and photosynthesis from MODIS 8‐day composites for the most part followed the pattern and magnitude of CO 2 exchange observed at the tower.

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

A GH3-like gene, CcGH3, isolated from Capsicum chinense L. fruit is regulated by auxin and ethylene* - Kede Liu; Byoung-Cheorl Kang; Hui Jiang; Shanna L. Moore; Hanxia Li; Christopher B. Watkins; Tim L. Setter; Molly M. Jahn (Plant Molecular Biology, 2005)

Patterns of nitrogen and sulfur accumulation and retention in ombrotrophic bogs, eastern Canada - Tim Moore; Christian Blodau; Jukka Turunen; Nigel Roulet; Pierre J. H. Richard (Global Change Biology, 2005)
Nitrogen (N) and sulfur (S) play important roles in peatlands, through their influence on plant production and peat decomposition rates and on redox reactions, respectively, and peatlands contain substantial stores of these two elements. Using peat N and S concentrations and dry bulk density and 210 Pb dating, we determined the rates of N and S accumulation over the past 150 years in hummock and hollow profiles from 23 ombrotrophic bogs in eastern Canada. Concentrations of N and S averaged 0.80% and 0.18%, respectively, generally increased with depth in the profile and there was a weak but significant correlation between N and S concentrations. Rates of N and S accumulation over the past 50–150 years ranged from 0.5 to 4.8 g N m −2 yr −1 and from 0.1 to 0.9 g S m −2 yr −1 . There were significant but weak correlations between C, N and S accumulation rates over 50‐, 100‐ and 150‐year periods. Over the last 50 years, rates of S accumulation showed little differentiation between hummocks and hollows, whereas the pattern for N accumulation was more variable (hummock minus hollow rate ranged from −1 to +1.5 g N m −2 yr −1 ), with hummocks generally having a larger N accumulation rate, correlated with the rate of carbon (C) accumulation. There was a modest but significant positive correlation between 50‐year rates of N accumulation and wet atmospheric deposition of N measured between 1990 and 1996, with accumulation rates about four times that of wet deposition. The difference between deposition and accumulation of N is attributed to organic N deposition, dry deposition and N 2 fixation. A weaker, but still significant, correlation was observed between 50‐year S accumulation and 1990–1996 wet atmospheric S deposition, with about 75% of the deposited S accumulating in the peat. A laboratory experiment with peat cores exposed to varying water table position and simulated N and S deposition, showed that on average 87% and 98% of the deposited NH 4 + and NO 3 − , respectively, and 58% of the deposited S were retained in the vegetation and unsaturated zone of the cores, supporting the results from the field study.

A Case Study of Carbon Pools Under Three Different Land-Uses in Panam - Catherine Potvin; Edward Whidden; Tim Moore (Climatic Change, 2004)

Carbon dioxide and methane production potentials of peats from natural, harvested and restored sites, eastern Québec, Canada - Stephan Glatzel; Nathan Basiliko; Tim Moore (Wetlands, 2004)

Roles of moss species and habitat in methane consumption potential in a northern peatland - Nathan Basiliko; Roger Knowles; Tim R. Moore (Wetlands, 2004)

Experimental response of peatland carbon dynamics to a water table fluctuation - Christian Blodau; Tim R. Moore (Aquatic Sciences, 2003)

Tropical pasture carbon cycling: relationships between C source/sink strength, above‐ground biomass and grazing - Brian J. Wilsey; Gabrielle Parent; Nigel T. Roulet; Tim R. Moore; Catherine Potvin (Ecology Letters, 2002)
We measured net ecosystem CO 2 exchange (NEE) in Panamá over C 4 pasture plots that varied in grazing intensity. After adjusting for variation in light, there were noticeable effects of grazing‐related variables on CO 2 exchange that were largely dependent on the developmental stage of the plant canopy. Above‐ground productivity was positively related to grazing intensity ( r 2 =0.30). Two experimentally grazed fields had significantly lower standing crop biomass but no significant difference in CO 2 uptake (24.2 μmol/m 2 /s) compared with two ungrazed fields (20.3 μmol/m 2 /s). Grazed fields had significantly lower ecosystem respiration rates (10.3 μmol/m 2 /s) than did ungrazed fields (17.6 μmol/m 2 /s). These results suggest that, although these pastures were possible sources of CO 2 during the time intervals sampled, the size of the sources tended to be dampened by cattle grazing through reductions in ecosystem respiration. Thus, it appears that disturbance caused by cattle grazing will not always result in an increase in CO 2 release from tropical pastures to the atmosphere.

Modeling Northern Peatland Decomposition and Peat Accumulation - Steve Frolking; Nigel T. Roulet; Tim R. Moore; Pierre J. H. Richard; Martin Lavoie; Serge D. Muller (Ecosystems, 2001)

Urinary creatine profiles after administration of cell-specific testicular toxicants to the rat - Nigel P. Moore; Dianne M. Creasy; Tim J. B. Gray; John A. Timbrell (Archives of Toxicology, 1992)